The burden of hospitalization of road crash victims in a secondary health care facility in Oyo, Nigeria (2011)
The study examined the hospitalization burden of road crash (injured) victims in Oyo town. Primary data were collected through questionnaire administration and In-Depth interview. One-hundred crash victims were involved in the survey. Secondary data were sourced from the General hospital records. Descriptive statistics were used for data analysis. Findings indicated that 65% of road crash victims were males, about 87% of them were less than 50 years old and 85% earned not more than N10,000 per month. The length of stay (LOS) showed that each crash victims spent 39 days on the average in the hospital and incurred a daily expense of N750 throughout the victim stay in the hospital. The consequences included reduced income (18.9%), job loss (8.4%) and abandoned by friends and family members (16.8%) among others. The paper calls for improved pre-hospital trauma care and the establishment of Road Accident Fund in order to ameliorate the burden of road crash victims.